THE CONCEPT OF THE ISLAMIC EDUCATION MODEL IN THE TIME OF THE PROPHET SAW AND RECONSTRUCTION FOR THE PRESENT TIME: Konsep Model Pendidikan Islam di Masa Rasulullah SAW dan Rekonstruksi untuk Masa Sekarang - Zaman, Badrus; Mursyada, Ria Khasna (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2024)
This study aims to discuss the concept of the Islamic education model during the time of Prophet Muhammad and its reconstruction for the present era. It encompasses Islamic education conducted during two periods, namely the Makkah and Madinah periods, along with the values for reconstructing Islamic education applicable in the modern era. The author employed a literature review method, drawing data from journals, books, and relevant references related to the discussed topic. The study's findings indicate that in reconstructing Islamic education, attention must be given to the harmony of teaching methods. This includes the integration of digital platforms, specialized applications, and artificial intelligence to support learning. Strengthening character education can be achieved through practical learning methods, character-based projects, and collaborative learning. Moreover, holistic Islamic scholarship emphasizes spiritual, intellectual, social, and moral aspects. By adopting the values and methods of Islamic education from the time of Prophet Muhammad and formulating a curriculum aligned with the needs of the current era, it is hoped that contemporary Islamic education can provide a profound and sustainable understanding for learners.